“Late sodium current: a mechanism for angina, heart failure, and arrhythmia” - Makielski, Jonathan C. (J Cardiovasc Pharmacol, 2009)
The peak sodium current underlies excitability and conduction in heart muscle, but a late sodium current flowing after the peak contributes to maintaining and prolonging the action potential plateau, and also to intracellular sodium loading, that in turn increases intracellular calcium with consequent effects on arrhythmia and diastolic function. Late sodium current is pathologically increased in both genetic and acquired heart disease, making it an attractive target for therapy to treat arrhythmia, heart failure, and angina. This review provides an overview of the underlying bases for the clinical implications of late sodium current block.